Accountability and the Law Rights, Authority and Transparency of Public Power - Mikuli, Piotr; Kuca, Grzegorz (Comparative Constitutional Change, 2022)
"This book discusses contemporary accountability and transparency mechanisms by presenting a selection of case studies. The authors deal with various problems connected to controlling public institutions and incumbents' responsibility in state bodies. The work is divided into three parts. Part I: Law examines the institutional and objective approach. Part II: Fairness and Rights considers the subject approach, referring to a recipient of rights. Part III: Authority looks at the functional approach, referring to the executors of law. Providing insights into increasing understanding of various concepts, principles, and institutions characteristic of the modern state, the book makes a valuable contribution to the area of comparative constitutional change. It will be a valuable resource for academics, researchers, and policy-makers working in the areas of constitutional law and politics."